Determinants of saving behaviour among employees in Kelantan / Nor Azira Abd Aziz - Abd Aziz, Nor Azira (2012)
This paper investigates the relationship of income level, credit availability and interest rate effects saving behavior among employee. The target population of this study was employees in area of Kota Bharu, Kelantan and use primary data (questionnaire) as data collection method. A convenience sampling technique use to target 75 respondents. The research design use in this is hypothesis testing framework. There are three independent variables (income level, interest rate and credit availability) use to test either it have significant to the dependent variable (saving). For data analysis, the finding shows that income level and interest rate has significant relationship with saving behavior. Meanwhile, credit availability not has significant relationship with saving behavior